2014
DOI: 10.1002/jbmr.2209
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Mortality and BMI After Fracture: A Population-Based Study of Men and Women Aged ≥40 Years

Abstract: Fractures in obese older individuals contribute significantly to the overall burden on primary health care, but data on their impact on mortality are lacking. We studied the association between obesity and mortality following hip and nonhip clinical fractures in a retrospective, population-based cohort study. The Sistema d'Informacio pel Desenvolupament de la Investigacio en Atencio Primària (SIDIAP Q ) database contains primary care computerized medical records of a representative sample of >2.1 million peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 65 publications
(72 reference statements)
3
34
1
Order By: Relevance
“…Analyzing the population health database from the family strategy program SIDIAP ® (Catalunya, Spain), Prieto-Alhambra and cols., described longer survival of overweight and obese individuals than normal weight subjects (18.5 to < 25 kg/m 2 ) after incident clinical fracture (57). This observation is consistent with other reports of the "obesity paradox" in conditions such as congestive cardiac failure, chronic renal insufficiency and chronic obstructive pulmonary disease (58)(59)(60)(61).…”
Section: Fracture Morbidity and Mortality In Obese Individualssupporting
confidence: 88%
“…Analyzing the population health database from the family strategy program SIDIAP ® (Catalunya, Spain), Prieto-Alhambra and cols., described longer survival of overweight and obese individuals than normal weight subjects (18.5 to < 25 kg/m 2 ) after incident clinical fracture (57). This observation is consistent with other reports of the "obesity paradox" in conditions such as congestive cardiac failure, chronic renal insufficiency and chronic obstructive pulmonary disease (58)(59)(60)(61).…”
Section: Fracture Morbidity and Mortality In Obese Individualssupporting
confidence: 88%
“…Recent literature suggests that obesity is protective against hip fractures and is associated with decreased mortality, the so called "obesity paradox" [36][37][38][39][40]. However, an analysis conducted across fracture sites in this study demonstrated that isolated femoral neck fractures were signifi cantly associated with mortality in this cohort of orthopaedic trauma patients.…”
Section: Discussioncontrasting
confidence: 64%
“…Because obese and overweight patients often fare better than their normal-weight counterparts, the tag "obesity paradox" has often been applied. As shown in Figures 8A and B, obese patients who have uninfected fractures of the hip or other bones show better outcomes that are reminiscent of those observed with so-called unconquerable infections (48). Valentijn et al compiled a collection of published reports of surgical entities and a similar collection of nonsurgical entities where patients with above-normal adiposity show better outcomes (49,50).…”
Section: Evidence From Animal Studiesmentioning
confidence: 99%